2021
DOI: 10.1101/2021.03.15.435478
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single amino acid polymorphism in a conserved effector of the multihost blast fungus pathogen expands host-target binding spectrum

Abstract: Accelerated gene evolution is a hallmark of pathogen adaptation and specialization following host-jumps. However, the molecular processes associated with adaptive evolution between host-specific lineages of a multihost plant pathogen remain poorly understood. In the blast fungus Magnaporthe oryzae (Syn. Pyricularia oryzae), host specialization on different grass hosts is generally associated with dynamic patterns of gain and loss of virulence effector genes that tend to define the distinct genetic lineages of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 102 publications
(161 reference statements)
0
8
0
Order By: Relevance
“…The different pOPIN-GG acceptors are crosscompatible for co-expression, allowing for ease of co-expression and purification of protein complexes. Finally, the utility of the pOPIN-GG vectors presented here have already been successfully tested by the community for the expression and purification of a fungal effector from Parastagonospora nodorum (Outram et al, 2021), as well as for detailing the structural mechanisms underpinning the evolution of Magnaporthe oryzae effectors for a specific host target (Bentham et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The different pOPIN-GG acceptors are crosscompatible for co-expression, allowing for ease of co-expression and purification of protein complexes. Finally, the utility of the pOPIN-GG vectors presented here have already been successfully tested by the community for the expression and purification of a fungal effector from Parastagonospora nodorum (Outram et al, 2021), as well as for detailing the structural mechanisms underpinning the evolution of Magnaporthe oryzae effectors for a specific host target (Bentham et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The Pik NLR pair occurs as allelic series in both Japonica and Indica rice cultivars (Chaipanya et al, 2017; Costanzo and Jia, 2010; Hua et al, 2012; Xu et al, 2008). The AVR-Pik effectors are also polymorphic and present signatures of selection (Bentham et al, 2021; Bialas et al, 2018; Yoshida et al, 2009). Allelic Pik NLRs have differential recognition specificities for the AVR-Pik variants (De la Concepcion et al, 2021; Kanzaki et al, 2012), which is underpinned by differential effector binding to the Pik-1 HMA domain (De la Concepcion et al, 2018; De la Concepcion et al, 2021; Maqbool et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, very few of these studies have specifically focused on how effectors evolve to maintain their function in the context of a new cellular environment. A recent study looked at effector-target co-evolutionary dynamics in the blast fungus Magnaporthe oryzae (10). The authors identified a highly conserved effector, APikL2, that is present across all assayed host-specific pathogen lineages (10).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study looked at effector-target co-evolutionary dynamics in the blast fungus Magnaporthe oryzae (10). The authors identified a highly conserved effector, APikL2, that is present across all assayed host-specific pathogen lineages (10). They found that a single naturally-occurring amino acid polymorphism in APikL2 expands the range of host targets that this effector can bind to, and conclude that the mutation is likely adaptive in the lineages where it is found (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation